2000
DOI: 10.1162/089892900562183
|View full text |Cite
|
Sign up to set email alerts
|

Brain Indices of Music Processing: “Nonmusicians” are Musical

Abstract: Abstract& Only little systematic research has examined event-related brain potentials (ERPs) elicited by the cognitive processing of music. The present study investigated how music processing is influenced by a preceding musical context, affected by the task relevance of unexpected chords, and influenced by the degree and the probability of violation. Four experiments were conducted in which

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

83
587
6
23

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 461 publications
(699 citation statements)
references
References 37 publications
83
587
6
23
Order By: Relevance
“…However, the early syntax-related anterior negativity, although being lateralized to the left in a number of studies (Friederici, Mecklinger, & Hahne, 1996;Friederici, Pfeifer, & Hahne, 1993;Hahne & Friederici, 1999), not always demonstrates a clear left maximum but sometimes shows a bi-lateral distribution (Friederici, von Cramon, & Kotz, 1999;Kn€ o osche, Maess, & Friederici, 1999). An early anterior negativity with a right hemisphere dominance (ERAN) was found for violations of syntax-like disharmonic patterns in music (K€ o olsch, Gunter, & Friederici, 2000). Musical features such as frequency, rhythm, and intonation also appear in natural speech and are called the prosodic cues of spoken language which have been shown to be important factors of speech comprehension (Kimberly, Lindfield, Wingfield, & Goodglass, 1999) at the segmental and suprasegmental level.…”
Section: Introductionmentioning
confidence: 99%
“…However, the early syntax-related anterior negativity, although being lateralized to the left in a number of studies (Friederici, Mecklinger, & Hahne, 1996;Friederici, Pfeifer, & Hahne, 1993;Hahne & Friederici, 1999), not always demonstrates a clear left maximum but sometimes shows a bi-lateral distribution (Friederici, von Cramon, & Kotz, 1999;Kn€ o osche, Maess, & Friederici, 1999). An early anterior negativity with a right hemisphere dominance (ERAN) was found for violations of syntax-like disharmonic patterns in music (K€ o olsch, Gunter, & Friederici, 2000). Musical features such as frequency, rhythm, and intonation also appear in natural speech and are called the prosodic cues of spoken language which have been shown to be important factors of speech comprehension (Kimberly, Lindfield, Wingfield, & Goodglass, 1999) at the segmental and suprasegmental level.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies investigated this field with linguistic stimuli, and recently, this field was considerably expanded by the investigation of music processing. Studies with electroencephalography (EEG) revealed that harmonically inappropriate chords presented within a sequence of chords elicit brain responses with a latency of around 180-400 ms that are maximal over the right hemisphere (Patel et al, 1998;Koelsch et al, 2000bKoelsch et al, , 2001aKoelsch et al, ,b, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies from Koelsch et al (2000bKoelsch et al ( , 2001aKoelsch et al ( ,b, 2002, chord-sequences (each consisting of 5 chords) were composed in a classical style (and according to the rules of part-writing) and presented to both non-musicians (Koelsch et al, 2000b(Koelsch et al, , 2001b(Koelsch et al, , 2002 and musicians (Koelsch et al, 2001a). Harmonically inappropriate chords elicited an early right anterior negativity (ERAN) that was clearly visible over both hemispheres, although right preponderant, and which had a maximal amplitude around 200 ms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations